A mechanical-diffusive peridynamics coupling model for meso-scale simulation of chloride penetration in concrete under loadings. (30th April 2020) - Li, Wanjin; Guo, Li
Highlights: A mesoscopic mechanical-diffusive peridynamics coupling model was constructed. Chloride penetration into cracked concrete could be simulated efficiently. The effects of loadings on chloride diffusion increase with the increasing stress level. Abstract: A coupled mechanical-diffusive peridynamics (PD) model is developed to simulate chloride penetration in saturated concrete under various loadings at meso-scale. PD is implemented in the architecture of finite element method (FEM) and truss elements are used to substitute for the PD bonds. In the coupled model, damage evolution and crack growth in concrete under loadings and chloride penetration into concrete with updated diffusivity caused by cracks can be investigated simultaneously. At each coupling step, the quasi-static mechanical analysis is conducted by solving the equilibrium equations, while the forward differencing method is adopted for chloride diffusion. Several numerical examples are carried out to validate the proposed PD models in terms of addressing mechanical-diffusive problems. The numerical results coincide with the test findings and clearly indicate that the width and depth of cracks can influence the chloride diffusivity when "threshold crack width" is reached. Additionally, the chloride diffusivity increases with the increase of stress level under high compressive, tensile and flexural stress levels.